Conditions that enable effective feedback. Issue 7 (10th November 2019) - Henderson, Michael; Phillips, Michael; Ryan, Tracii; Boud, David; Dawson, Phillip; Molloy, Elizabeth; Mahoney, Paige
ABSTRACT: Despite an increasing focus on assessment feedback, educators continue to find that simply replicating an effective feedback practice from one context does not guarantee success in the next. There is a growing recognition that the contextual factors surrounding successful practices need to be considered. This article reports on a large-scale mixed methods project and proposes 12 conditions that enable successful feedback in higher education. The conditions were distilled from seven rich case studies through multiple stages of thematic analysis, case comparison and reliability checking. The conditions were also evaluated by surveying senior leaders of Australian universities. These conditions highlight the importance of carefully designing feedback processes, along with the need for addressing capacity and culture for feedback. This helps to explain why there are such variances in effective feedback across contexts, and offers insight into how it may be achieved.